Employer-Sponsored Health Insurance and the Promise of Health Insurance Reform - Thomas C. Buchmueller; Alan C. Monheit (SAGE Publishing, 2009)
The central role that employers play in financing health care is a distinctive feature of the U.S. health care system, and the provision of health insurance through the workplace has important implications well beyond its role as a source of health care financing. In this paper, we consider the "goodness of fit" of employer-sponsored health insurance (ESI) in the current economic and health insurance environments and in light of prospects for a vigorous national debate over the shape of health care reform. The main issue that we explore is whether ESI can have a viable role in health system reform efforts or whether such coverage will need to be significantly modified or even abandoned as reform seeks to address important issues in the efficient provision and equitable distribution of health insurance coverage.